INTERNET-BANKING AS THE WAY OF REMOTE BANKING SERVICE IN RUSSIA - T.K. MEDVEDSKAYA (Advanced Engineering Research)
The article is based on the research of diversification of banking services with the use of information technologies (IT). It concerns such important innovation as online banking. The time history of electronic banking in Russian banks is examined in the article as one of the most promising ways of Internet banking.